A NEW OPTIMIZED IMPLEMENTATION OF A FAST INTRA PREDICTION MODE DECISION ALGORITHM FOR HEVC STANDARD - Touzani, Hajar; Wali, Ibtissem; Errahimi, Fatima; Mansouri, Anass; Masmoudi, Nouri; Ahaitouf, Ali (International Journal of Computing, 2020)
New and stronger video compression standard was developed during the last years, called H.265/HEVC (High Efficiency Video Coding). This standard has undergone several improvements compared to H.264/AVC (Advanced Video Coding). In intra prediction block, 33 directional intra prediction modes were included in H.265 to have an efficient coding instead of 8 modes that were used in H.264 in addition to planar and DC modes, which has generated computational complexities in the new standard. Therefore one of the most issues for embedded implementation of HEVC is time reduction of the encoding process. In this paper, an embedded implementation of a fast intra prediction algorithm is performed on ARM processors under the embedded Linux Operating System. Experimental results included the comparison between the original HM16.7 and the proposed algorithm show that the encoding time was reduced by an average of 61.5% with an increase of 1.19 in the bit rate and a small degradation in the PSNR of 0.05%.